Physical Activity and Individual Health - Jabarova Dilora; Sattarava Hulkar Gairatovna (Zien Journals, 2022)
The question is what is olive oil used for? I can answer this question simply with olive oilrecord holder for lowering cholesterol, which means it is indispensable for the prevention of atherosclerosis, cardiovascular diseases, diabetes, anti-inflammatory effect, Alzheimer's disease and other ailments. The results of the study proved that olive oil (Olea europaea) contains oleic acid in a large amount of acid that reduces the level of bad cholesterol. The main component of vegetable oil is nigellon, which is a derivative of the two substances dithymoquinone and thymoquinone. Herbal teas (hepalux and hepafit (improves liver function) antioxidant, cleansing (cleanses the body of toxins) cardionorm, phytotonometer (to improve heart function and against hypertension) phyto slim turbo iodine (in lack of iodine and for weight loss cleansing the body of toxins) and others herbal teas
Keywords: squapen; ecdysterone; polyaza; dopamine